Plutarch’s Themistocles: The Serpent of Hellas - Finn, Jennifer (Histos, 2020)
In Plutarch’s <emThemistocles, the general and expatriate is thrice referenced using snake imagery. This article argues that Plutarch deliberately uses snake motifs at loaded points in the narrative to express the transformations of the general’s image in Athenian social memory, and to direct his reader towards a certain interpretation of the general’s legacy. In the centuries between the Persian Wars and the composition of Plutarch’s Lives, Themistocles had been variously represented in Athenian memory as both a patriot and a traitor, often with reference to serpentine imagery that may have been initially propagated by the general himself. An analysis of other snake references—as well as characterisations of Themistocles—in Plutarch’s works reveals that such symbolism was both structurally consistent and à propos in the context of understanding the past as a lesson for contemporary imperial Roman politics.